Development of a risk indicator score card for a large, flight training department. (November 2020) - Anderson, Carolina L.; Aguiar, Marisa D.; Truong, Dothang; Friend, Mark A.; Williams, Jason; Dickson, MacKenzie T.
Highlights: Safety Performance Indicators used to create a monthly risk indicator score card. Twelve Safety Performance Indicators drawn from flight and maintenance operations. Risk indicator score card quantifies risk for large flight training department. Risk score card increases accuracy of flight department's Safety Management System. Abstract: The purpose of the research was to create and validate a single, quantitative indicator of flight risk for a Title 14 of the Code of Federal Regulations (CFR) Part 141 flight training department to increase the accuracy of the Risk Management and Safety Assurance components of the department's Safety Management System (SMS). The researchers created and validated, via expert elicitation, a non-statistical model composed of twelve Safety Performance Indicators (SPIs) from both flight and maintenance operations and their relevant formulas. These were based on two years of flight-performance data from a 14 CFR Part 141 flight training department in the Southeast United States. Once the SPIs had been quantified, standardized, and assigned a weighted value, they were used to create a Risk Indicator Score Card capable of portraying the risk associated with flight operations; maintenance operations; and overall, combined operations on a monthly basis.